ORGANIC CARBON IN THE UPPER LAYER OF OCEAN-FLOOR SEDIMENTS - Romankevich Ye.A.; Bobyleva N.V. (My University, 1990)
Organic matter (OM) that is deposited on the bottom as a component of suspended matter derived chiefly from upper ocean layers greatly affects the processes of sedimentation and lithogenesis there. The most reliable information on the concentration and the distribution of OM in ocean sediments is provided by determinations of organic carbon (Corg) and by corresponding maps of its distribution. Our new map of the distribution of Corg concentrations in percent of air-dry matter (subsequently called the percentage-concentration map for short, Fig. 1) was compiled mainly from earlier published maps supplemented by numerous data recently obtained by Soviet and foreign authors. The five zones with different Corg concentrations shown on this map are based on about 8000 Corg determinations made by the Knopp-Fresenius methods, as well as by the method of dry high-temperature combustion with the Corg content directly determined from organic CO2. They fairly well reflect the main distribution patterns on OM in the upper layer of bottom deposits.